2017
DOI: 10.1167/iovs.16-20339
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Subconjunctival Delivery of Infliximab Protects the Cornea and Retina Following Alkali Burn to the Eye

Abstract: PurposeTumor necrosis factor (TNF)-α is upregulated in eyes following corneal alkali injury and contributes to corneal and also retinal damage. Prompt TNF-α inhibition by systemic infliximab ameliorates retinal damage and improves corneal wound healing. However, systemic administration of TNF-α inhibitors carries risk of significant complications, whereas topical eye-drop delivery is hindered by poor ocular bioavailability and the need for patient adherence. This study investigates the efficacy of subconjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 32 publications
1
75
0
1
Order By: Relevance
“…IL-1β and TNFα are two key pro-inflammatory cytokines involved in inflammatory reactions. Their levels are upregulated after corneal injury and overactive IL-1β and TNFα exaggerate corneal inflammation and impair wound healing [ 22 26 ]. To determine whether Sirt6 could directly regulate inflammation in corneal epithelial cells, we specifically reduced Sirt6 protein levels using siRNA knockdown in cultured primary human corneal epithelial cells in vitro and determined their response to IL-1β and TNFα.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1β and TNFα are two key pro-inflammatory cytokines involved in inflammatory reactions. Their levels are upregulated after corneal injury and overactive IL-1β and TNFα exaggerate corneal inflammation and impair wound healing [ 22 26 ]. To determine whether Sirt6 could directly regulate inflammation in corneal epithelial cells, we specifically reduced Sirt6 protein levels using siRNA knockdown in cultured primary human corneal epithelial cells in vitro and determined their response to IL-1β and TNFα.…”
Section: Resultsmentioning
confidence: 99%
“…Optic nerve cross sections were processed using a modified paraphenylenediamine (PPD) staining protocol to stain the myelin sheath of all axons and the axoplasma of damaged axons, as previously described ( 66 ). Optic nerves were fixed with half-strength Karnovsky’s fixative [2% formaldehyde + 2.5% glutaraldehyde in 0.1 M sodium cacodylate buffer, pH 7.4 (Electron Microscopy Sciences)] for a minimum of 24 h at 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the therapeutic efficacy of anti-VEGF DDS in corneal NV reduction, an established corneal NV model was used. 21,25,30 CNV analysis revealed that superior CNV was completely inhibited with anti-VEGF DDS throughout the study period (Figs. 3Q, 3S), (P < 0.05 mixed ANOVA).…”
Section: Anti-vegf Dds Inhibits Corneal Neovascularization After Cornmentioning
confidence: 98%
“…Immunohistochemical evaluation was performed as previously described. 21 Primary antibodies diluted in 1% bovine serum albumin were incubated with the tissue samples overnight at 4°C, followed by secondary antibody incubation for two hours at room temperature. Detail information of the antibodies is provided in the Supplementary Methods section.…”
Section: Histological and Immunohistochemical Evaluation Of The Corneamentioning
confidence: 99%
See 1 more Smart Citation